Awareness and barriers of blood donation among first year undergraduate students in school of health sciences, Universiti Sains Malaysia - Rohaizat, Siti Aisyah Eddy (Universiti Sains Malaysia, 2024)
Blood donation is an essential public health activity that is vital for saving lives. However, the current number of volunteer donors is inadequate to fulfil the increasing need. Gaining insight into the various degrees of consciousness and recognizing obstacles to blood donation among young individuals is crucial for formulating focused strategies to enhance donation rates. The objective of this study is to measure the level of awareness and determine the perceived barriers that prevent first-year undergraduate students in the School of Health Sciences at Universiti Sains Malaysia (USM) from donating blood. This study aimed to evaluate the level of awareness and identify the main barriers to blood donation among first-year undergraduate students in the School of Health Sciences at Universiti Sains Malaysia (USM). The results revealed that 77.5% of respondents demonstrated good awareness of blood donation. The primary barrier identified was "I am not eligible because of medical reasons," reported by 24.7% of participants. There was a statistically no significant association between awareness and barriers to blood donation (p-value = 0.251), leading to the accepting of the null hypothesis. However, no significant association was found between age and barriers to blood donation (p-value = 0.401), resulting in the acceptance of the null hypothesis. Additionally, a significant association was observed between gender and barriers to blood donation, thus rejecting the null hypothesis. These findings underscore the need for targeted interventions to address specific barriers and enhance blood donation awareness among students. The study emphasizes the importance of awareness in lowering the barriers on blood donation among first year undergraduate students in School of Health Science, Universiti Sains Malaysia (USM). USM can foster a more conducive environment for blood donation by addressing identified barriers through targeted educational efforts, psychological support, and increased accessibility, thereby contributing to the larger public health goal of maintaining a steady and reliable blood supply.